Społeczna odpowiedzialność firm a partycypacja pracownicza - Jasińska, Jolanta (Corporate Social Responsibility and Employee Participation, 2009)
The issue of CSR is strictly connected with employee participation. The success in this scope without employee involvement is impossible. The article emphasizes the significance of participation in this process. Moreover, some facilitating and distracting activities within the process of introducing such practices is discussed as well.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 42, s. 151-156